Correction: Hotspots of human impact on threatened terrestrial vertebrates. - James R Allan; James E M Watson; Moreno Di Marco; Christopher J O'Bryan; Hugh P Possingham; Scott C Atkinson; Oscar Venter (PLoS Biology)
[This corrects the article DOI: 10.1371/journal.pbio.3000158.].